2016
DOI: 10.18203/issn.2455-4510.intjresorthop20162871
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic resection of dorsal wrist ganglion

Abstract: INTRODUCTIONGanglions are the most common causes of focal masses of the hand and wrist. They arise from the synovium of joints or tendon sheaths. Dorsal wrist ganglion is the most common type of ganglion arising from the hand.1 The exact etiology is not known and the most common site of origin is the dorsal scapho-lunate ligament. A one way valve is believed to exist which allows the fluid to enter the swelling from the joint and appear most commonly between the second and fourth extensor tendon compartment.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Many previous research articles studied the effectiveness of honey against MRSA [58], [59], [11], [60], [61]. For example, a previous study revealed that, the MIC of honey was between 15 and 20% v/v for the MRSA isolates [10]. Furthermore, five types of honey against MRSA were found to be active against MRSA but with varying degrees with general MIC and MBC range values observed between 8.33 and 33.3% (w/v) [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous research articles studied the effectiveness of honey against MRSA [58], [59], [11], [60], [61]. For example, a previous study revealed that, the MIC of honey was between 15 and 20% v/v for the MRSA isolates [10]. Furthermore, five types of honey against MRSA were found to be active against MRSA but with varying degrees with general MIC and MBC range values observed between 8.33 and 33.3% (w/v) [58].…”
Section: Discussionmentioning
confidence: 99%
“…Honey consists mainly of sugars, water, minerals, and vitamins, especially B complex and vitamin C. Honey has been orally administrated for years due to their nutritional and therapeutic values; honey possesses anti-oxidant, anti-inflammatory, and anti-bacterial properties. Honey can overcome the multi-drug resistant bacteria [10]. Moreover, honey was able to overcome MRSA biofilms [11].…”
Section: Introductionmentioning
confidence: 99%